Computation of transcritical steady flow over a curved bed with lateral contraction - Cheng, Nian-Sheng (2012)
The St. Venant equations are adequate in simulating the free-surface flow over lightly curved beds, but are insufficient when applied to some moderately to highly curved flows caused by bed sills and lateral contractions. Many other studies have only considered effects of the changes in the channel bottom elevation. In comparison, the effect of the lateral contraction combined with the bottom change has not been thoroughly investigated. In this study, with the consideration of the pressure modification induced by the flow curvature, a one-dimensional equation is derived to compute the water surface profile for transcritical flows. The situation investigated is limited to the case of flows with a moderately curved bed combined with lateral contraction. The computational results show that the predicted flow profiles compare well with experimental data.